Access to effective but expensive treatments: An analysis of the solidarity argument in discussions on funding of medical treatments - van Till, Sietske A. L. (Bioethics, 2023)
The development of new effective but expensive medical treatments leads to discussions about whether and how such treatments should be funded in solidarity-based healthcare systems. Solidarity is often seen as an elusive concept; it appears to be used to refer to different sets of concerns, and its interrelations with the concept of justice are not well understood. This paper provides a conceptual analysis of the concept of solidarity as it is used in discussions on the allocation of healthcare resources and the funding of expensive treatments. It contributes to the clarification of the concept of solidarity by identifying in the literature and discussing four uses of the concept: (1) assisting patients in need, (2) upholding the solidarity-based healthcare system, (3) willingness to contribute and (4) promoting equality. It distinguishes normative and descriptive uses of the concept and outlines the overlap and differences between solidarity and justice. Our analysis shows that the various uses of the concept of solidarity point to different, even conflicting, ethical stances on whether and how access to effective, expensive treatments should be provided. We conclude that the concept of solidarity has a role to play in discussions on the accessibility and funding of newly approved medical treatments. It requires, for instance, that healthcare policies promote and maintain both societal willingness to contribute to the care of others and the value of providing care to vulnerable patients through public funding.